The effect of emotional advertising in a gender role: The case of Coca-Cola in Culiacán-Sinaloa - Lara Félix, Jesús Humberto; Díaz Martínez, Aurora; Becerra-Perez, Luis A. (Unidad Editorial UPTC, 2020)
The soft drink industry has led strong advertising strategies, investing large amounts of money in order to capture the attention of cola soda consumers. The objectives of this study are to identify and demonstrate that emotional advertising increases the intention to buy in fizzy drinks in consumers being the gender a unique factor in the level of liking. It was investigated in similar studies where the role of gender is a differentiating factor in the perception and changes in attitudes towards such advertising. For this study, Coca-Cola and a representative sample of 120 young people were analyzed to decode the effect of their advertising and analyze whether the ads promote the purchase action. As a research technique an experimental, transversal and descriptive methodology was used taking the sample for convenience in a random manner, in a faculty room it was conditioned comfortably and that nothing could affect the responses of the participants in the questionnaire that they answered, was divided into two parts,pres-test and post-test,in both parts they were questioned about their intention to buy fizzy drinks (Coca-Cola). Keywords: emotional advertising, gender effect, purchase intention, marketing. JEL Codes: M30, M31, M39 Received: 24/05/2019. Accepted: 28/04/2020.  Published: 24/05/2020